+0  
 
0
78
1
avatar

f(x)= 3x+7

g(x)=?

h(x)=3x+7/3x+9

(gof)(x)=3x+7/3x+9

(goh)(x)=...?

 

(i think g(x) = x/x+2....)

 

pls help me.. thank you

Guest Mar 2, 2018
 #1
avatar+87342 
+1

You are correct, g(x)  =  x  / [ x + 2]

 

So

 

(g ° h) x  =     g ( h(x))   =   

 

[ (3x + 7) / (3x + 9) ]  /  [ (3x + 7) / (3x + 9) + 2  ]   =

 

[ (3x + 7)/ (3x+9) ]  /  [   ( 2 (3x + 9) + (3x + 7) )  /  (3x + 9) ]  =

 

[ (3x + 7)/ (3x + 9) ]  /  [ (9x + 25) / (3x + 9) ]  =

 

3x + 7               3x + 9

_______   *      _______

3x + 9               9x + 25

 

 

  3x + 7

_______

  9x + 25

 

 

cool cool cool

CPhill  Mar 2, 2018

13 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.